Perovskite solar cells : simulations and optimization - Zhang Sihan (Nanyang Technological University, 2020)
This report is forces on the simulation and optimization of the perovskite solar cell (PSC). Perovskite solar cell is a type of photovoltaic device that is basedon the perovskite materials, and this report also touch in the research of different type of perovskite materials, due to perovskite solar cell has the high throughput, cheaper manufacturing cost and large volume, it become more popular in the research area, but due to lower power conversion efficiency and toxic of the perovskite contains toxic lead, it is not fully accepted by human until now. In this report, the structure and working principle of the perovskite solar cell are described. Three different types of perovskite materials which are CH3NH3BiXPb1‑XI3, CH3NH3PbI3and CH3NH3SnI3are comparedin the solar cell application. By varying the different layer’s thickness of the PSC structures, the operation of the PSC is simulated,and the device structure is optimized by comparing their calculated power conversion efficiency.